Positivisasi Hukum Islam di Indonesia Era Reformasi - Masruhan, Masruhan (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
The Islamic law in Indonesia has evolved from time to time in line with the demands of the changing history. Recently, and during the era of reformasiâit is commonly known soâthe Islamic law has been progressively positivised. By this we mean the dynamics within which the Islamic law has the ability to respond to the new situation that requires the re-thinking of some of its dictums. The role of the government has equally been good; it is completely supportive of this process. This shift in direction taken by Islamic law is due to the fact that the colonial law in the country has become rotten. It is no longer able to deal with the ever-changing situations of this Muslim-majority country. This paper discusses this historic turn, and embarks on the debate concerning the advantages of the Islamic law for a Muslim country like Indonesia. The paper also links this development with the democratic system that the country has adopted. It argues that democracy does serve as a pre-condition in which a revealed law like Syariâah can prevail.